RANCANG BANGUN APLIKASI RENTAL ALAT-ALAT PESTA DENGAN SISTEM NOTIFIKASI - Mohammad Faisol Zuhri; Siti Sufaidah; Agus Sifaunajah (SAINTEKBU, 2018)
Basically, every rental service is a business that serves to maintain, manage, and utilize rental tools that are then provided to customers. The development of this company, the need for technology is needed to support the work of the system to more quickly and efficiently in processing letters, bill notes and notes change goods, and displays notification information in the form of schedule events to facilitate the provision of information directly to all employees. Current conditions in the rental SUYONO in running its business activities have not used the information system technology so that in the operation of the operational activities are still slow. SUYONO rental requires an information system which will support its business activities. Information System users are not only used in information and communications technology (ICT) organizations but also used by companies to support their business activities. From some shortcomings that exist in the company then the researcher is interested to make a Rental Apparatus Party with the Notification System, so the rental SUYONO in performing its operations more easily and quickly. The existence of the application of party equipment rental can help SUYONO rental to process the data in accordance with the necessary needs, as well as Output results in the form of travel documents, the bill notes, change notes, and billing reports can speed up the presentation process. With the notification in the form of event schedule information displayed on the second screen can facilitate both for employees and office staff in providing information on the event schedule directly. Keywords: Information Systems, Party Equipment Rental, Notifications, SUYONO